Artery of Adamkiewicz and the clinical repercussion of its lesion in thoracoabdominal surgeries: a systematic review - de Sena, Idna Lara Goes; Lima, Maria Regina Cardoso Linhares Oliveira; Jereissati, Lia de Oliveira; da Costa, Rafaella Iughetti; Araújo, Victor Oliveira; de Oliveira, Isadora Mônica Ponte; Freitas, Lara Maria de Oliveira Paiva; Maia, Maria Victoria Rocha Fontenele; Lócio, Aline Moreira; dos Santos, Júlio César Claudino (Brazilian Journal of Case Reports, 2021)
The knowledge of the spinal cord irrigation is important for the therapeutic planning of aortic pathologies; however, its vasculature is complex due to the caliber of its arteries that pass through a three-dimensional network with great anatomical variability. Its clinical importance is evidenced during the preoperative procedure of thoracic and thoracoabdominal aortic surgeries, because its identification is essential for the prevention of spinal cord injuries. This study consists of a literature review, in which searches were conducted in the databases - Bireme, Science Direct, Pubmed and Lilacs. Articles published between 1999 and 2020, written in English, Portuguese or Spanish, were selected. The search was conducted using the descriptors Anatomy, Spinal Cord Irrigation and Spinal Cord Ischemia. The Adamkiewicz artery is the main artery responsible for the arterial supply to the lower part of the spinal cord. Thus, paraplegia is a complication of this type of surgical approach resulting from ischemic suffering of the spinal cord during the process. Therefore, further study on these factors should be encouraged, because the preservation of this vessel is relevant given the search for protection of the spinal cord and the maintenance of its functions in this type of procedure.